Serological cross reactivity between Glomerella cingulata and Camellia sinensis - S. GUHA; B.N. CHAKRABORTY*, U. CHAKRABORTY, R. DAS, P. BASU, (Indian Phytopathology, 2012)
Pathogenicity of G/omerella cingulata (Stoneman) Spauld and Schrenk, causal agent of brown blight disease, tested under identical conditions following detached leaf and cut shoot inoculation techniques against fourteen varieties of tea [Camellia sinensis (L.) a.Kuntze] revealed that CP-1 and TV-26 were resistant, while TV-18 and Teen Ali-17/1/54 were susceptible. Polyclonal antisera were raised separately against antigen preparations from mycelia and cell wall of G. cingulata (isolate Gc-1), mycelia of F. oxysporum and leaf antigens of TV-18 and CP-1. Cross reactive antigen (CRA) were found among the susceptible varieties of tea and isolates of G. cingulata (Gc- 1, 2 and 3). Such antigens were not detected between resistant varieties of tea and isolates of G. cingulata (Gc-1, Gc-2 & Gc-3 ); non-pathogen (Fusarium oxysporum) and tea varieties; isolates of G. cingulata and F. oxysporum and between non-host (Glycine max, Cicer arietinum and Camellia japonicum) and G. cingulata. Antisera raised against cell wall preparations gave better recognition than that against mycelial preparations as observed in ELISA test with antigens of tea leaves of different ages.